Poly(gamma-glutamylcysteinyl)glycine: its role in cadmium resistance in plant cells. - Jackson, P J (1987)
Angiosperms can be selected for the ability to grow in the presence of normally toxic concentrations of certain trace metal ions. Addition of Cd and Cu to Cd-resistant Datura innoxia cell cultures results in the rapid synthesis and accumulation of sulfur-rich, metal-binding polypeptides. The structure of these compounds was determined using amino acid analysis, 13C NMR, and site-specific enzymic digestion. These compounds are poly(gamma-glutamylcysteinyl)glycines. Greater than 80% of the cellular Cd is bound to the bis and tris forms in Cd-resistant cells. There is a direct correlation between the maximum accumulation of the metal-binding polypeptides and the concentration of toxic ions to which the cells are resistant. In the presence of metal ions, the polypeptides form multimeric aggregates that can be resolved by gel chromatography. Cd binds to both the high and low molecular weight aggregates, whereas Cu preferentially binds to the higher molecular weight forms. The presence of gamma-carboxamide linkages between glutamyl and adjacent cysteinyl residues indicates that these polypeptides are products of biosynthetic pathways. Poly(gamma-glutamylcysteinyl)glycines bind metals and, in this respect, appear to be functional analogs of the protein metallothionein. However, in the absence of supraoptimal concentrations of trace metal ions, the functions of metallothionein in animals and microorganisms and poly(gamma-glutamylcysteinyl)glycines in plants may differ.